Breach of Obligations: Assumptions for Compensation and Heads of Recoverable Damages - Orúe Cruz, José René (Scientific journal of social studies, 2026)
This article critically analyzes the regime of breach of contract in Nicaraguan Civil Law, with an emphasis on the assumptions of compensation, the components of recoverable damages, and the liability of the debtor acting in good faith. Based on a study of the provisions of the Nicaraguan Civil Code, legal doctrine, and the jurisprudence of the Supreme Court of Justice, supplemented by comparative law references, the limitations of the system are examined, particularly in defining recoverable damages. It is argued that criteria such as foreseeability and the notion of necessary consequence generate interpretive uncertainty and can limit full compensation. This work seeks to highlight these situations and contribute to a more coherent and critical application of contractual civil liability.